Mechanistic insights into the pathogenesis of microtubule‐targeting agent‐induced peripheral neuropathy from pharmacogenetic and functional studies - Chua, Katherina C. (2022)
Chemotherapy-induced peripheral neuropathy (CIPN) is a common dose-limiting toxicity that affects 30%-40% of patients undergoing cancer treatment. Although multiple mechanisms of chemotherapy-induced neurotoxicity have been described in preclinical models, these have not been translated into widely effective strategies for the prevention or treatment of CIPN. Predictive biomarkers to inform therapeutic approaches are also lacking. Recent studies have examined genetic risk factors associated with CIPN susceptibility. This review provides an overview of the clinical and pathologic features of CIPN and summarizes efforts to identify target pathways through genetic and functional studies. Structurally and mechanistically diverse chemotherapeutics are associated with CIPN; however, the current review is focused on microtubule-targeting agents since these are the focus of most pharmacogenetic association and functional studies of CIPN. Genome-wide pharmacogenetic association studies are useful tools to identify not only causative genes and genetic variants but also genetic networks implicated in drug response or toxicity and have been increasingly applied to investigations of CIPN. Induced pluripotent stem cell-derived models of human sensory neurons are especially useful to understand the mechanistic significance of genomic findings. Combined genetic and functional genomic efforts to understand CIPN hold great promise for developing therapeutic approaches for its prevention and treatment.